Family–school partnerships in the age of Covid-19: reasons for optimism amidst a global pandemic. Issue 2 (3rd July 2021) - Jones, Chris; Forster, Colin
ABSTRACT: This article reports on research undertaken in May and June 2020, during the initial phase of the Covid-19 pandemic when schools in England were still closed to the majority of children. The research sought to explore the impact of the so-called 'lockdown' on family–school partnerships. Research shows such partnerships make an important contribution to the effective education of children and young people, potentially leading to improved behaviour, engagement and learning outcomes. The study was conducted as a short online survey, circulated through social media and email, which invited teachers, school leaders and others working in primary and secondary schools to share their experiences of family–school partnership during this time. Analysis of the data showed that schools had made considerable efforts to maintain communication and support for all families, particularly those deemed 'hard-to-reach', and many participants reported that family–school partnerships had actually been strengthened through this testing period of time.